PENSION PROs (planning for your golden years) / Fathimah Asyakirah Norhisham ... [et al.] - Norhisham, Fathimah Asyakirah; Mohd Zain, Nor Ain Natasha; Abd Razak @ Sulimin, Nur Atiqah; Mohd Zaidi, Siti Nur Fatma; Hashim, Nurhaslinda (Universiti Teknologi MARA, Kedah, 2023)
PENSION PROs application is designed to prepare the user for their retirement years. Today’s potential retirees are facing many challenges to plan their money for immediate needs as well as for their future needs. As there is a shift in the economic situation, financial planning plays an important role in minimizing the exposure. With an easy and flexible interface, this application offers features that help the user to plan money in an encouraging manner. Before any user is able to plan for future financial, our application will identify their spending patterns. Users can oversee their spending contribution based on their current statement. At the same time, this application provides information for a realistic spending plan. Thus, it can provide the ideal spending limit to avoid overspending their money. In addition, this application comes out with a simple calculator for users to track their spending and retirement savings. PENSION PROs also offer interfaces to help users for their investment and portfolio planning. Users can track their current investment and portfolio return as well as potential financial assets that are suitable for them. At the same time, this application offers a surface for any financial institutions to market and promote their products and services suitable for potential retirees. The combination of investment savvy with informative spending tracking makes our user can use one application for their personal needs in retirement years.